2018
DOI: 10.1177/0040517518801189
|View full text |Cite
|
Sign up to set email alerts
|

Facile fabrication of superhydrophobic and superoleophilic glass-fiber fabric for water-in-oil emulsion separation

Abstract: Superhydrophobic and superoleophilic glass-fiber fabric with high water-in-oil emulsion separation efficiency was prepared by a simple sol-gel process using MTES (triethoxymethylsilane) as precursor. The surface chemical composition, micromorphology, pore size distribution, thermal stability, and the wetting behavior of the glass-fiber fabric were characterized using scanning electron microscopy, Fourier transform infrared spectroscopy, capillary flow porometry, thermogravimetric analysis, and water (pH ¼ 1-14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…21 Specifically, the peak at 1017 cm −1 is responsible for the Si−O−Si group and 1409 cm −1 for other types of oxides (boron oxide, aluminum oxide, calcium oxide, and so on), which are the specific chemical compositions of the glass fiber. 22 There are also a few weaker bonds found at 1654 and 1409 cm −1 , which are related to water adsorptions occurring during the composite manufacturing process. 21 In Figure 5 b,c, the peaks around 3340 cm −1 may be attributed to the bonding between the external hydrogen in glassy structures and cellulosic structures (flax) −OH groups.…”
Section: ■ Results and Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…21 Specifically, the peak at 1017 cm −1 is responsible for the Si−O−Si group and 1409 cm −1 for other types of oxides (boron oxide, aluminum oxide, calcium oxide, and so on), which are the specific chemical compositions of the glass fiber. 22 There are also a few weaker bonds found at 1654 and 1409 cm −1 , which are related to water adsorptions occurring during the composite manufacturing process. 21 In Figure 5 b,c, the peaks around 3340 cm −1 may be attributed to the bonding between the external hydrogen in glassy structures and cellulosic structures (flax) −OH groups.…”
Section: ■ Results and Discussionmentioning
confidence: 98%
“…The broad bands ranging from 1017 to 3340 cm –1 (Figure a) represent the glassy material-based composites . Specifically, the peak at 1017 cm –1 is responsible for the Si–O–Si group and 1409 cm –1 for other types of oxides (boron oxide, aluminum oxide, calcium oxide, and so on), which are the specific chemical compositions of the glass fiber . There are also a few weaker bonds found at 1654 and 1409 cm –1 , which are related to water adsorptions occurring during the composite manufacturing process .…”
Section: Resultsmentioning
confidence: 99%
“…The treated fabric shows better oil/water separation, water-in-oil and oil-in-water emulsion separation properties, even after various harsh treatments ( Figure 13). Xu et al [136] produced a superhydrophobic and superoleophilic glass-fiber fabric by a simple sol-gel process using triethoxymethylsilane (MTES) as precursor. The prepared fabric can effectively separate micron-sized surfactant-stabilized water-in-oil emulsions solely driven by gravity.…”
Section: Oil and Water Separationsmentioning
confidence: 99%
“…When a vigorously stirred mixture of hexane-water was poured onto the treated cotton fabric, hexane immediately spread and freely permeated through the fabric at atmospheric pressure and, rapidly accumulated into the bottom of the beaker. It can be clearly seen in Figure 15 that there was no water in the Xu et al [136] produced a superhydrophobic and superoleophilic glass-fiber fabric by a simple sol-gel process using triethoxymethylsilane (MTES) as precursor. The prepared fabric can effectively separate micron-sized surfactant-stabilized water-in-oil emulsions solely driven by gravity.…”
Section: Oil and Water Separationsmentioning
confidence: 99%
“…Although it has been widely demonstrated that superhydrophobicity can be imparted to glass materials, the fabrication of superhydrophobic glass fibers is still unsatisfactory in terms of cost efficiency, durability, and processability, which significantly hinders their practical applications. Most of the current reports include amino-silica particle synthesis and trimethoxymethylsilane reflux methods, which involve complex and time-consuming processes and cannot readily be adapted to produce large-scale or complex three-dimensional surfaces [33][34][35] .…”
Section: Robust and Continuous Oil/water Separation With Superhydrophmentioning
confidence: 99%